Keto-polymethines: a versatile class of dyes with outstanding spectroscopic properties for in cellulo and in vivo two-photon microscopy imaging. Issue 1 (30th August 2016) - Pascal, Simon; Denis-Quanquin, Sandrine; Appaix, Florence; Duperray, Alain; Grichine, Alexei; Le Guennic, Boris; Jacquemin, Denis; Cuny, Jérôme; Chi, San-Hui; Perry, Joseph W.; van der Sanden, Boudewijn; Monnereau, Cyrille; et al.
Abstract : The keto-heptamethine family has been expanded to various symmetrical and asymmetrical structures. Abstract : The synthesis of keto-heptamethine derivatives has been expanded to various new symmetrical and asymmetrical structures, including an unprecedented di-anionic keto-polymethine. The spectroscopic behavior of these new dyes has been systematically and thoroughly investigated, revealing that the formation of hydrogen bond interactions with protic solvents is responsible for a dramatic enhancement of the fluorescence quantum yield in the far-red spectral region. The existence of these strong hydrogen-bond interactions was further confirmed by molecular dynamics simulations. These bis-dipolar polymethines exhibit large two-photon absorption (TPA) cross-sections ( σ 2 in GM) in the near-infrared, making them ideal candidates for NIR-to-NIR two-photon microscopy imaging applications. We demonstrate that the molecular engineering of the hydrophilic/hydrophobic balance enables targeting of different cellular components, such as cytoplasm or cell membranes. Addition of appropriate substituents provides the molecule with high-water-solubility, affording efficient two-photon probes for angiography.